SCIB2, an antibody DNA vaccine encoding NY-ESO-1 epitopes, induces potent antitumor immunity which is further enhanced by checkpoint blockade - Xue, Wei; Metheringham, Rachael L.; Brentville, Victoria A.; Gunn, Barbara; Symonds, Peter; Yagita, Hideo; Ramage, Judith M.; Durrant, Lindy (Taylor & Francis, 2016)
Checkpoint blockade has demonstrated promising antitumor responses in approximately 10-40% of patients. However, the majority of patients do not make a productive immune response to their tumors and do not respond to checkpoint blockade. These patients may benefit from an effective vaccine that stimulates high-avidity T cell responses in combination with checkpoint blockade. We have previously shown that incorporating TRP-2 and gp100 epitopes into the CDR regions of a human IgG1 DNA (ImmunoBody®: IB) results in significant tumor regression both in animal models and patients. This vaccination strategy is superior to others as it targets antigen to antigen-presenting cells and stimulates high-avidity T cell responses. To broaden the application of this vaccination strategy, 16 NY-ESO-1 epitopes, covering over 80% of HLA phenotypes, were incorporated into the IB (SCIB2). They produced higher frequency and avidity T cell responses than peptide vaccination. These T cells were of sufficient avidity to kill NY-ESO-1-expressing tumor cells, and in vivo controlled the growth of established B16-NY-ESO-1 tumors, resulting in long-term survival (35%). When SCIB2 was given in combination with Treg depletion, CTLA-4 blockade or PD-1 blockade, long-term survival from established tumors was significantly enhanced to 56, 67 and 100%, respectively. Translating these responses into the clinic by using a combination of SCIB2 vaccination and checkpoint blockade can only further improve clinical responses.